From “The Mother of the Litoral” to “Dead City”. Continuities, Popular Agencies and Decline of Cobija in its Chilean Stage (1877-1931) - Galaz-Mandakovic Fernández, Damir (Universidad Academia de Humanismo Cristiano, 2022)
The present work is committed to overcoming that formalist view of international historiography that closes the history of the port of Cobija (former Bolivian port) in the triennium of 1877 and 1879. We present the background to affirm that the port was not completely erased in that triennium, especially marked by earthquake, tidal wave and war. It is shown that the definitive decline of Cobija has to do with the emergence of the Gatico mineral (10 kilometers north of Cobija), a mineral that was industrialized in 1905, generating a territorial transformation in economic, demographic and political terms. The other process that we want to analyze refers to the coup de grace that Cobija received in 1913 through a nationalist community agency in Tocopilla that prevented the resurgence of the port through a project related to Chuquicamata and the Guggenheim family of New York, which sought revitalize the deteriorating port. In addition, we are committed to understanding the territory of Cobija and its adjacency zone as a territory defined by open traffic and population mobility, which in practice meant a demographic dispersion in very close mines, which also leads us to reconsider and reflect on the ways of accounting for the population in what was the commune of Cobija.